Nevirapine Significantly Reduces the Levels of Racemic Methadone and (R)-Methadone in Human Immunodeficiency Virus-Infected Patients - Stocker, Hartmut (American Society for Microbiology, 2004)
Methadone is metabolized by various isoforms of the cytochrome P450 family, which can be induced by many drugs, including nevirapine. The objective of the present study was to determine the effects of coadministration of nevirapine and methadone on the dose-adjusted areas under the concentration-time curves (AUCs) of racemic and (R)-methadone. Twenty-five human immunodeficiency virus-infected subjects taking stable single daily doses of racemic methadone or (R)-methadone were included in this prospective, single-crossover trial. At the baseline, nevirapine was either started as part of a new regimen containing two nucleoside reverse transcriptase inhibitors (NRTIs) or added to an ongoing NRTI regimen. Patients could increase their methadone doses if withdrawal symptoms developed. Twelve-hour pharmacokinetic profiles were obtained before and 28 days after the start of nevirapine treatment. The total concentrations of methadone and its inactive metabolite, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP), in serum were determined by liquid chromatography-tandem mass spectrometry. Among the 20 evaluable patients, coadministration of nevirapine significantly decreased the mean dose-adjusted AUC of methadone by 41%. AUC reductions were similar for patients taking racemic methadone (37%; n = 11) and (R)-methadone (44%; n = 9). AUC changes ranged from mild increases in three patients to decreases of up to 70%. Fourteen of 20 patients required additional methadone due to withdrawal symptoms. However, the median dose increase was only 15%, which was less than that which would have been expected from the pharmacokinetic data. The AUC of EDDP increased significantly, by 35%. Methadone dose adjustments are justified when methadone is coadministered with nevirapine. Due to extensive variability, the adjustments must be tailored to the individual patient's needs.